Talking story: eBooks to improve reading comprehension skills / Basitah Amirah and Aminabibi Saidalvi - -, Basitah Amirah; Saidalvi, Aminabibi (Academy of Language Studies, 2023)
This study developed a set of e-books to enhance reading comprehension skills among Form Four and Five students in one of the secondary schools in Sarawak, Malaysia. The set of eBooks entitled 'Talking Story' was designed using the 21st Century teaching and learning techniques, in which interactivity and animation were incorporated to attract students' interest and enhance their reading comprehension skills. The e-books aimed to instil the love of reading in students. A total of twenty-eight participants, eight males and twenty females, were selected using simple random cluster sampling by the English language coordinator of the school. Prior to collecting data, a need analysis was carried out to identify the features of a good e-book that will interest the students. Using a quantitative research approach, a set of questionnaires was distributed to the students after using the e-book and data was analysed descriptively. It was found that all the students strongly agreed using the Talking Story e-book enhanced their interest in reading and were more ready to attempt reading comprehension questions in their SPM English paper. The implication of the findings will encourage students and teachers to use interactive materials like Talking Story e-book in enhancing reading comprehension skills. Future studies are encouraged to develop eBook materials to improve reading comprehension skills.